2017
DOI: 10.3892/ol.2017.7254
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gli1‑mediated prostate cancer cell proliferation by inhibiting the mTOR/S6K1 signaling pathway

Abstract: Abstract. Ectopic activation of the canonical Hedgehog signaling pathway is involved in the development and progression of prostate cancer, which is one of the leading causes of cancer-associated mortality in males worldwide. However, the role of the non-canonical Hedgehog signaling pathway in prostate cancer remains generally unexplored. In the present study, it was identified that Gli (glioma-associated oncogene)1 and Gli2 were highly expressed at the protein level in the androgen-independent prostate cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…GANT61 inhibits GLI1/2-controlled luciferase expression at high doses (IC 50 ≈ 10 µM), abolishes GLI1-regulated genes [ 206 ] and subsequent megakaryocytic differentiation [ 207 ]. GANT61 also induces apoptosis in many cancer and leukemia models such as gastric cancer [ 208 ], Ewing sarcoma [ 209 ], biliary tract cancer [ 210 ], lung cancer [ 211 ], breast cancer [ 212 , 213 ], prostate carcinoma [ 214 , 215 ] and adult T-cell leukemia or acute myeloid leukemia [ 216 , 217 ]. GANT61 induces autophagy in pancreatic ductal adenocarcinoma cells and prevents cellular migration in osteosarcoma metastasis [ 218 ] and ovarian and breast cancer invasion [ 212 , 219 ].…”
Section: Targeting Transcription Factor Through a Binding Pocketmentioning
confidence: 99%
“…GANT61 inhibits GLI1/2-controlled luciferase expression at high doses (IC 50 ≈ 10 µM), abolishes GLI1-regulated genes [ 206 ] and subsequent megakaryocytic differentiation [ 207 ]. GANT61 also induces apoptosis in many cancer and leukemia models such as gastric cancer [ 208 ], Ewing sarcoma [ 209 ], biliary tract cancer [ 210 ], lung cancer [ 211 ], breast cancer [ 212 , 213 ], prostate carcinoma [ 214 , 215 ] and adult T-cell leukemia or acute myeloid leukemia [ 216 , 217 ]. GANT61 induces autophagy in pancreatic ductal adenocarcinoma cells and prevents cellular migration in osteosarcoma metastasis [ 218 ] and ovarian and breast cancer invasion [ 212 , 219 ].…”
Section: Targeting Transcription Factor Through a Binding Pocketmentioning
confidence: 99%
“…Melanomas critically require HH signaling [ 27 , 28 , 29 ], presumably with activated RAS-MAPK and AKT signaling cascades [ 27 ]. HH has been described to promote oncogenesis in leukemias [ 30 , 31 , 32 , 33 , 34 ], bladder cancer [ 35 ], and prostate cancer [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, it was found that medulloblastoma resistance towards SMO inhibitors decreased as a result of combination therapy with SMO and PI3K/AKT inhibitors [ 83 ], and recently, the combination of the SMO inhibitor, NVP-LDE-225 with the PI3K/mTOR inhibitor, NPV-BEZ-235 exhibited improved efficacy towards inhibition of self-renewal and tumorigenicity of human pancreatic cancer stem cells, compared to treatment with only one of the agents, [ 84 ]. Furthermore, inhibition of PI3K/mTOR by NPV-BEZ-235 was shown to inhibit GLI1-dependent proliferation of androgen-independent prostate cancer cells [ 85 ]. Whereas the majority of prostate cancers depends on androgens (testosterone) during the initial stage, the cancer cells progressively lose the dependency on androgens during the advanced stages; thus, the cancer cells become resistant to hormonal treatments [ 86 ].…”
Section: Mechanisms Leading To Hh/mtor Crosstalkmentioning
confidence: 99%
“…Whereas the majority of prostate cancers depends on androgens (testosterone) during the initial stage, the cancer cells progressively lose the dependency on androgens during the advanced stages; thus, the cancer cells become resistant to hormonal treatments [ 86 ]. Interestingly, the authors found that the protein levels of GLI1 and GLI2 were highly increased in the androgen-independent prostate cancer cell lines PC3 and DU145 but not in the androgen-dependent cancer cell line LNCaP [ 85 ].…”
Section: Mechanisms Leading To Hh/mtor Crosstalkmentioning
confidence: 99%